2001
DOI: 10.1096/fj.00-0641fje
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide selectively releases metals from theN‐terminal domain of metallothioneins: potential role at inflammatory sites

Abstract: Metallothioneins (MTs) and various other metal binding proteins release metals when exposed to nitric oxide (NO). We investigated the structural consequences of the interaction between MTs and NO by using 1H‐ and 113Cd‐NMR spectroscopy and found that only the three metals from the N‐terminal β‐domain were selectively released whereas the C‐terminal α‐domain remains intact. Since it has been proposed that the β‐domain is responsible for the postulated role of MTs in zinc homeostasis, whereas the tight binding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
89
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 48 publications
6
89
1
2
Order By: Relevance
“…Rather high concentrations of NO are needed to observe significantly reduced cadmium levels in MT2, which corroborates the role of MTs in heavy metal detoxification as a result of rather tight binding of cadmium to MTs [18,19]. The maximum number of metals released from Cd 5 Zn 2 -MT2 at the highest NO concentrations used in these ICPMS studies amount to 1.5 Zn and 3.25 Cd per MT2 molecule, which shows that in contrast to mouse MT1, [31] significant amounts of metal are also set free from the a-domain.…”
Section: Sec-icpmssupporting
confidence: 75%
See 1 more Smart Citation
“…Rather high concentrations of NO are needed to observe significantly reduced cadmium levels in MT2, which corroborates the role of MTs in heavy metal detoxification as a result of rather tight binding of cadmium to MTs [18,19]. The maximum number of metals released from Cd 5 Zn 2 -MT2 at the highest NO concentrations used in these ICPMS studies amount to 1.5 Zn and 3.25 Cd per MT2 molecule, which shows that in contrast to mouse MT1, [31] significant amounts of metal are also set free from the a-domain.…”
Section: Sec-icpmssupporting
confidence: 75%
“…2) clearly show that the release of both cadmium and zinc by NO is suppressed completely by GSH, but not GSSG. As already suggested in our previous paper [31], zinc is more readily released than cadmium. Rather high concentrations of NO are needed to observe significantly reduced cadmium levels in MT2, which corroborates the role of MTs in heavy metal detoxification as a result of rather tight binding of cadmium to MTs [18,19].…”
Section: Sec-icpmssupporting
confidence: 71%
“…7 and 23). Evidence is available suggesting that the binding sites of MT, particularly those that comprise the N-terminal (␤-cluster) metal-binding domain of the protein (24), may be the ultimate recipients of zinc ions lost from the plasma pool during stress and inflammation. Although IL-6 has been shown to enhance the induction of MT in hepatocytes (8,9,25), our data presented here suggest that both Zip14 and MT are components of the IL-6-mediated hypozincemia.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is needed for microbial pathogenicity (5,35), and a hypozincemia may limit zinc availability. Zn 2ϩ mobilization induced by nitric oxide may also be an explanation for the up-regulation of Zip14 during inflammation and infection (24). Zinc influences cytokine production by leukocytic populations in vivo and in vitro (36,37) and may be of therapeutic value during sepsis (38).…”
Section: Discussionmentioning
confidence: 99%
“…2 The free radical nitric oxide (NO) can form stable complexes with MT, inducing conformational changes in the protein and the selective release of metals (e.g., zinc). 3 S-nitrosation of the MT sulphydryl groups, the mechanism responsible for the loss of metal from the binding centers of the protein, 4 is also a key event of NO signaling. 5 Stitt et al demonstrated that the metal responsive transcription factor MTF-1 required for the activation of genes, including the MT genes involved in the cell response to various stresses, is one of the cellular target of the zinc released from metallothionein and it has been hypothesized that the release of zinc caused by NO might act as a novel signal transduction pathway participating in the cell response to oxidative stress.…”
Section: Metallothionein and Nitric Oxide Signalingmentioning
confidence: 99%